2002
DOI: 10.1046/j.1356-9597.2001.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of PRMT1 with BTG/TOB proteins in cell signalling: molecular analysis and functional aspects

Abstract: Background : Several recent reports have connected protein methylation with differentiation. Furthermore, the BTG/TOB proteins have also been implicated in such control. BTG1 and 2 have been shown to interact with PRMT1 (predominant cellular arginine N-methyltransferase of type I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 46 publications
6
88
0
Order By: Relevance
“…However, we failed to observe any potentiation of TRa/BTG1 transcriptional activity by PRMT1 coexpression, in agreement with inability of BTG1 to interact with PRMT1 in the presence of TRa (data not shown). We obtained similar data indicating that PRMT1 does not affect CMD1/ BTG1 transcriptional activity, a result well supported by the observation that PRMT1 and CMD1 recognize a common BTG1 sequence (C box; Berthet et al, 2002;present data), thus precluding an interaction including the three proteins. In addition, in these experiments, we unexpectedly found that PRMT1 is probably to be considered as a CMD1 coactivator.…”
Section: Btg1 Is a Coactivator Of Positive Regulators Of Myoblast Difsupporting
confidence: 72%
See 1 more Smart Citation
“…However, we failed to observe any potentiation of TRa/BTG1 transcriptional activity by PRMT1 coexpression, in agreement with inability of BTG1 to interact with PRMT1 in the presence of TRa (data not shown). We obtained similar data indicating that PRMT1 does not affect CMD1/ BTG1 transcriptional activity, a result well supported by the observation that PRMT1 and CMD1 recognize a common BTG1 sequence (C box; Berthet et al, 2002;present data), thus precluding an interaction including the three proteins. In addition, in these experiments, we unexpectedly found that PRMT1 is probably to be considered as a CMD1 coactivator.…”
Section: Btg1 Is a Coactivator Of Positive Regulators Of Myoblast Difsupporting
confidence: 72%
“…Instead, we found that the BTG1 A box, a well-conserved sequence in all members of the BTG family, with an unknown function prior to this study, interacts both with TRa1 and CMD1. In addition, whereas the C box, already shown to interact with PRMT1 (Berthet et al, 2002), is specifically involved in the physical interaction with CMD1, the 129-171 BTG1 C-terminus interacts with TRa1. Therefore, recruitment of various transcription factors by BTG1 involves several domains of the protein.…”
Section: Btg1 Is a Coactivator Of Positive Regulators Of Myoblast Difmentioning
confidence: 99%
“…First, TIS21 interacts with protein-arginine N-methyltransferase (PRMT1, Lin et al 1996;Berthet et al 2002) and it acts as a substrate of arginine methyltransferase (Lim et al 1998b). BTG2 /TIS21 also interacts with murine homolog of yeast CAF1 protein (Rouault et al 1998), homeoprotein Hoxb9 (Prevot et al 2000) and hCAF1/hPOP2 (Prevot et al 2001).…”
Section: Proteins Interacting With Tis21mentioning
confidence: 99%
“…In addition, both Btg1 and Btg2 proteins have been shown to interact with and stimulate the activity of protein arginine methyltransferase-1 (PRMT1), the major arginine methyltransferase in mammals (Lin et al, 1996;Berthet et al, 2002). Protein arginine methylation is an emergent posttranslational modification involved in a growing number of cellular processes, including transcriptional regulation, cell signaling, DNA repair, and RNA processing (Robin-Lespinasse et al, 2007).…”
Section: Discussionmentioning
confidence: 99%